Sensitization to, and allergic contact dermatitis caused by, colophonium in north‐eastern Italy in 1996 to 2016 with a focus on occupational exposures. (4th September 2018) - Mauro, Marcella; Fortina, Anna Belloni; Corradin, Teresa; Marino, Alessandro; Bovenzi, Massimo; Filon, Francesca Larese
Abstract : Background: Colophonium is a natural substance derived from Pineaceae trees. It is used in a wide range of consumer and occupational products because of its tackiness, and is a known sensitizer. Objectives: To analyse the temporal trend of contact allergy to colophonium in north‐eastern Italy, and to evaluate the associations with occupations in our geographical area. Methodology: From 1996 to 2016, 27 381 patients with suspected allergic contact dermatitis were patch tested in north‐eastern Italy. Individual characteristics were documented by use of a standardized questionnaire in 6 departments of dermatology or occupational medicine. Results: The overall prevalence of colophonium sensitization was 1.67%; the prevalence was significantly higher in women (1.75%) than in men (1.49%). No significant differences among departments were observed. We found significant associations between colophonium sensitization and being a student (odds ratio [OR] 4.64; 95% confidence interval [CI]: 1.04‐20.6), being a farmer or fishermen (OR 3.63; 95%CI: 1.21‐10.84), being a housekeeper (OR 2.02; 95%CI: 1.08‐3.77), and being retired (OR 2.06; 95%CI: 1.08‐3.92). Conclusion: Our study showed that contact allergy to colophonium is still relevant in north‐eastern Italy. The frequency of sensitization has dropped significantly over a period of 10 years, but students and farmers/fishermen still have sensitization prevalences above 3.5%. Our results are in line with European data.